Utilization Of Language Learning Strategies By Iranian Post-Graduate Students And Their Attitude And Motivation Toward Learning English - Pezeshkian, Fatemeh (2010)

(untitled)
This study investigated utilization of language learning strategies by Iranian postgraduate students and the influence of motivation and attitude on the students’ use of language learning strategies. Kerman province was selected according to cluster sampling. Then, 156 second semester post-graduate students in Kerman province were included in the present study. Data were collected through language learning strategy questionnaire developed by Oxford (1997) and Attitude/Motivation Test Battery (AMTB) adapted from Zarafshan (2002). Descriptive statistics showed that Iranian post-graduate students were high strategy users. The respondents reported the use of metacognitive, affective, compensation, social, cognitive, and memory respectively based on the frequency of use while cognitive and memory strategies were reported at a medium level and other strategies were reported at a high level. Descriptive statistics also indicated that Iranian post-graduate students had positive attitude toward learning English. Although students with positive attitude utilized the strategies more than students with negative attitude, independent sample T-test showed that attitude did not have a significant influence on utilization of language learning strategies. To determine motivation level of students, mean score for each motivation level was calculated. It showed that Iranian postgraduate students were instrumentally motivated rather than integratively motivated. It was indicated that integratively motivated students utilized strategies more than instrumentally motivated ones except for memory strategy. However, t-test indicated that instrumental motivation increased the use of memory strategies while integrative motivation increased the use of cognitive strategy. Other differences were not found to be significant. To determine the use of strategies by students of art and science, mean scores of both groups of students in strategy utilization were calculated. It showed that Arts students utilized strategies more than Science students. Overall, t-test showed that the Arts and Science majors had a statistical significant influence [t= 0.546] on the choice of cognitive strategy.